Increased risk of adenomatous colon polyps in patients with long-term use of proton pump inhibitors: a single-center retrospective study - Na Rae Lim; Woo Chul Chung (Journal of Yeungnam Medical Science)
Background It is unclear whether long-term use of proton pump inhibitors (PPIs) has a potential carcinogenic effect on the colorectum. Methods We reviewed a consecutive series of neurosurgery outpatients who underwent two or more colonoscopies between January 2014 and April 2023. Patients in whom the timing of endoscopy was not in accordance with the guidelines and those without a history of previous endoscopy were excluded. In the second colonoscopy, the risk of adenomatous colon polyps was evaluated depending on whether the patient had taken a PPI. Results In total, 520 patients were enrolled. In the multivariate analysis related to the risk of adenomatous colon polyps, age and aspirin use for >5 years were identified as significant factors. After excluding patients who had taken aspirin for >5 years, the patients were divided into three groups: those who had taken PPIs for >12 months, those who had taken PPIs for >3 months but <12 months, and those who had not taken PPIs. The risk of adenomatous colon polyps in these groups was 35.2%, 32.8%, and 22.8%, respectively (p=0.10). In the post-hoc analysis, there was a significant difference between patients who took PPIs and those who did not (p=0.03). In the multivariate analysis, a history of PPI use for >12 months was a significant risk factor for the development of advanced colon polyps (p=0.03). Conclusion Prolonged PPI use appears to increase the risk of developing adenomatous and advanced colon polyps.